Development and Validation of the CARRA-VID Prognostic Score: C Reactive Protein to Albumin Ratio, Red Blood Cell Distribution Width and Age-Based Score for Prognostication of Hospitalized COVID-19 Patients - Marko Lucijanic; Nevenka Piskac Zivkovic; Nikolina Busic; Josip Stojic; Armin Atic; Lovorka Derek; Ivan Krecak; Bruno Barsic; Ivica Luksic (Viruses)
Patients hospitalized due to coronavirus disease 2019 (COVID-19) usually present with severe or critical intensity of symptoms, accompanied by a marked systemic inflammatory response. Classical inflammatory biomarkers, C-reactive protein (CRP), albumin, and red blood cell distribution width (RDW) have previously been reported to be prognostic in hospitalized COVID-19 patients. We performed a retrospective analysis of two large cohorts (2305 and 2328 patients, respectively) of consecutive hospitalized COVID-19 patients with mostly severe and critical symptoms admitted to the tertiary referral center to develop and validate a prognostic score for 30-day mortality based on CRP-to-Albumin-Ratio (CAR), RDW, and age (termed CARRA-VID score). We identified 6 prognostic categories: very low, low, intermediate-1, intermediate-2, high, and very high risk, with corresponding 30-day mortality rates of 2.7%, 10.7%, 30.9%, 47.1%, 61.9%, and 89.7%, respectively. Effective risk stratification was validated in an independent cohort of patients and remained independent of the World Health Organization-defined disease severity and other commonly utilized risk scores. Additional analyses evaluated the score across different time periods dominated by distinct viral variants. We also present a simplified 3-tiered version of the score. A Microsoft Excel Workbook containing the score calculator is provided.